Design and implementation of a health document - Mazouz, Sanae; Cherkaoui Malki, Ouçamah Mohammed; Nfaoui, El Habib (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Exchanging and integrating medical information in the healthcare domain is a challenge. Indeed, the diversity of databases and the different representations of information sources make this exchange a very difficult task. Divers standards, (e.g. HL7: Health Level Seven; DICOM: Digital Imaging and Communication in Medicine), are created to enable the exchange and make health information systems interoperable. However, applying standardization requires changing the structure of existing healthcare systems. Our main purpose is to create a health document for exchanging health information between heterogeneous systems without applying changes on the internal structure of systems. The document uses the XML language to allow a structured and flexible exchange of healthcare data. The proposed health document can make the exchange of healthcare data among heterogeneous health information systems simpler and efficient. This document addresses the problem of interoperability between health information systems. The paper summarizes standards used to support interoperability in healthcare domain and propose a health document to enable the exchange of medical information across heterogeneous and distributed health information systems without requirements or adjustment on their systems.